Merawat Keberagamaan di Balik Perdebatan Kopi dan Rokok - Syamsun Ni’am (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2015)
Diversity is naturally taken for granted, Allah the God creates the universe and enriches it by diversity itself. Human beings as part of the creation of Gods should be able to nurture the diversity. In reality, one cannot live without considering the plurality of things. For that reason, wisdom is needed to show mutual respect in the context of diversity and differences. The good example of maintaining the diversity is to learn theutterances as well as best practices undertaken by the predecessor and the founding fathers of this nation.Ihsan of Kediri East Java is one example of Sufi teacher who thougt such wisdom. Although he passed Islamic education by nonformal way, he has successfully written his monumental work, Irshad al-Ikhwan li Baya Shurb al-Qahwah wa al-Dukhan which discusses the legal aspect of coffee and cigarettes. The most important thing is not regarding with his ijtihad onwhether coffee and cigarettes are halal, haram, and makruh, but the implications of his ijtihad that urges Muslim to appreciate and respect to other different cultures. This is much more important to be implemented, because there are now many thoughts and movements that negating thedifference and diversity which arises at any time.